Improvement of Rat Spinal Cord Injury Following Lentiviral Vector-Transduced Neural Stem/Progenitor Cells Derived from Human Epileptic Brain Tissue Transplantation with a Self-assembling Peptide Scaffold - Abdolahi, Sara (Mol Neurobiol, 2021)
Spinal cord injury (SCI) is a disabling neurological disorder that causes neural circuit dysfunction. Although various therapies have been applied to improve the neurological outcomes of SCI, little clinical progress has been achieved. Stem cell–based therapy aimed at restoring the lost cells and supporting micromilieu at the site of the injury has become a conceptually attractive option for tissue repair following SCI. Adult human neural stem/progenitor cells (hNS/PCs) were obtained from the epileptic human brain specimens. Induction of SCI was followed by the application of lentiviral vector-mediated green fluorescent protein–labeled hNS/PCs seeded in PuraMatrix peptide hydrogel (PM). The co-application of hNS/PCs and PM at the SCI injury site significantly enhanced cell survival and differentiation, reduced the lesion volume, and improved neurological functions compared to the control groups. Besides, the transplanted hNS/PCs seeded in PM revealed significantly higher migration abilities into the lesion site and the healthy host tissue as well as a greater differentiation into astrocytes and neurons in the vicinity of the lesion as well as in the host tissue. Our data suggest that the transplantation of hNS/PCs seeded in PM could be a promising approach to restore the damaged tissues and improve neurological functions after SCI.